1999
DOI: 10.1177/002215549904700111
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Localization of β-Actin and Amphoterin mRNA in Cultured Cells: Application of Tyramide Signal Amplification and Comparison of Detection Methods

Abstract: SUMMARYWe describe a nonradioactive preembedding in situ hybridization protocol using digoxigenin-labeled RNA probes and tyramide signal amplification to increase the sensitivity of detection. The protocol is sensitive enough for electron microscopic localization of endogenous messenger RNAs encoding ␤ -actin and amphoterin. Three visualization methods were compared: diaminobenzidine enhanced by nickel, Nanogold enhanced by silver and gold toning, and fluorescently labeled tyramides. Diaminobenzidine and Nanog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…The sections were subsequently exposed to preformed biotin-peroxidase/streptavidin complex for 30 minutes and the antigen-antibody complexes were visualized with 0.7 mM diaminobenzidine hydrochloride/0.002% H 2 O 2 in 0.05 M Tris HCl (pH 7.6). To increase the signal, 6 mg/ml ammonium-nickel sulphate was added to the diaminobenzidine–H 2 O 2 solution wherever indicated [23]. To confirm the specificity of immunohistochemical staining, the previously described control stainings were performed [9].…”
Section: Methodsmentioning
confidence: 99%
“…The sections were subsequently exposed to preformed biotin-peroxidase/streptavidin complex for 30 minutes and the antigen-antibody complexes were visualized with 0.7 mM diaminobenzidine hydrochloride/0.002% H 2 O 2 in 0.05 M Tris HCl (pH 7.6). To increase the signal, 6 mg/ml ammonium-nickel sulphate was added to the diaminobenzidine–H 2 O 2 solution wherever indicated [23]. To confirm the specificity of immunohistochemical staining, the previously described control stainings were performed [9].…”
Section: Methodsmentioning
confidence: 99%
“…However, studies in our laboratory have suggested that localization of amphoterin mRNA to the cell periphery might be a key step in bypassing nuclear transport of amphoterin. Localization of amphoterin mRNA shares similar features with β ‐actin mRNA localization, and these two mRNA particles are often found in cell processes together with ribosomes suggesting local mode of translation [18, 65]. Thus, mechanisms controlling localization of amphoterin mRNA might also be important regulators of secretion of amphoterin.…”
Section: Expression and Secretion Of Amphoterinmentioning
confidence: 99%
“…Then sections were incubated with DAB and H 2 O 2 , rinsed, counterstained, and mounted as described in the ABC-DAB method. In some cases, 6 mg/ml ammonium-nickel sulfate was added to the DAB-H 2 O 2 solution as recommended by Punnonen et al (1999). The solution was filtered when cloudy.…”
Section: Avidin-biotin Complex With Diaminobenzidine (Abc-dab)mentioning
confidence: 99%
“…In particular, catalyzed signal amplification (CSA) based on the deposition of labeled tyramide after activation by conversion of H 2 O 2 by peroxidase conjugated with an antibody has greatly increased the sensitivity of IHC and ISH methods (for reviews see Totos et al 1997;Speel 1999;Speel et al 1999). The method was originally developed for ELISA and Western blotting (Bobrow et al 1989(Bobrow et al ,1991(Bobrow et al ,1992 and has been adapted for light microscopy (LM) (Adams 1992;Kerstens et al 1995;Raap et al 1995;Van Gijlswijk et al 1996) and electron microscopy (EM) (Schöfer et al 1997;Bendayan 1997,1999;Punnonen et al 1999). The best detection systems for the CSA technique are at present the diaminobenzidine reaction with nickel enhancement or fluorescence for LM and Nanogold-silver staining for EM (Punnonen et al 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation